A new species of Helmutkunzia Wells & Rao, 1976 from an intertidal sandy beach in Xiamen, China and proposal of Pseudobalucopsylla gen. nov. (Copepoda, Harpacticoida, Miraciidae) - Mu, Fanghong; Huys, Rony (Zootaxa, 2021)
A new species of the genus Helmutkunzia Wells & Rao, 1976 (Miraciidae) is described from specimens collected from an intertidal sandy beach in Xiamen, Fujian Province, China. Helmutkunzia xiamenensis sp. nov. differs from its two congeners by the length/width ratio of the female P5 exopod, the number or length of the setae on the sexually dimorphic P2 endopod in the male and the relative length of the spines on the endopodal lobe of the male P5. The Chinese species is morphologically closest to H. variabilis Wells & Rao, 1987 from the Andaman and Nicobar island chain. Females of both species can readily be differentiated by the relative length of the P5 exopod while males can be differentiated by the length of the armature elements on P2 enp-2 and the endopodal lobe of P5. The genus Balucopsylla Rao, 1972 is reviewed, resulting in the proposal of Pseudobalucopsylla gen. nov. to accommodate the type species Balucopsylla triarticulata Wells & Rao, 1987 and three new Indo-Pacific species previously identified with it: P. obscura sp. nov. from the Andaman Islands, P. costaricensis sp. nov. from the Pacific coast of Costa Rica and P. mielkei sp. nov. from the Galápagos archipelago. A key to species of Pseudobalucopsylla sp. nov. is provided.